Munasabah Al-Qur'an with Textual Relation Approach Salwa M.S. El-Awwa: a Study of Surah Al-Qiyamah - Imam Maksum; Zaenal Arifin; Yor Hananta (JIE (Journal of Islamic Education), 2024)
The qur'an is the word of Allah that has a mutually supportive relationship to convey divine messages with a complex arrangement and structure and is full of wisdom. The approach used by Salwa M.S. el-Awwa provides a new perspective on understanding munasabah by emphasizing the importance of in-depth textual analysis to find patterns and relationships between verses. This article describes El-Awwa's thoughts on understanding the meaning between verses through a rational textual approach. This study uses a qualitative approach with a library research method to analyze and understand the concept of munasabah in the qur'an, especially in surah al-qiyamah, using a textual relational approach developed by Salwa M.S. El-Awwa. Data collection techniques use two main methods. First, a literature review includes collecting and reviewing books, articles, and scientific works related to munasabah, a textual relational approach, and surah al-qiyamah, including the works of Salwa M.S. El-Awwa and other academic references. Second, a review of tafsir works, namely reviewing classical and contemporary tafsir. The results of this study refer to the al-qiyamah verse, which can be concluded that pragmatically, this verse explains how serious the consequences are for people who close themselves off from the Prophet's call